Literasi dan Edukasi: Meningkatkan Pemahaman Masyarakat terhadap Ekonomi Syariah di Indonesia - Oktafianur, Muhammad Dodi; Rahmayanti, Selvia Dinda; Azizah, Tiara Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
As a country with the largest Muslim population in the world, Indonesia has the potential to become one of the centers of Islamic financial and economy at the regional and global levels. This potential needs to be balanced with a good and comprehensive understanding in the fields of Islamic economics and finance so that its distribution is not spread evenly throughout the region. Indonesia has a large market potential, so Indonesia must be the main driver of the Islamic economy. The research approach uses a descriptive qualitative approach with the literacy method. Research data analysis is focused on Islamic financial literacy. Data collection in this study is to use primary and secondary data. Islamic economic and financial literacy consists of several elements, the identification of the first element starts from the term financial literacy. The conception of financial literacy consists of two major parts, namely the element of mastery of financial knowledge and the implementation element of financial knowledge itself. Then the next step is to make the conception of financial literacy more comprehensive. In terms of external, Indonesia has opportunities to develop literacy and Islamic economic human resources. However, as for the challenges in developing the Islamic economy in Indonesia. One of them is the wrong understanding that Islamic financial products can only be accessed by people who are Muslim. This understanding is actually not true, because Islamic financial products can be accessed by anyone, not limited to certain religions.